Advance of genetically modified pigs in xeno-transplantation - Deng, Jiacheng; Yang, Lin; Wang, Ziru; Ouyang, Hongsheng; Yu, Hao; Yuan, Hongming; Pang, Daxin (Frontiers in Cell and Developmental Biology, 2022)
As the standard of living improves, chronic diseases and end-stage organ failure have been a regular occurrence in human beings. Organ transplantation has become one of the hopes in the fight against chronic diseases and end-stage organ failure. However, organs available for transplantation are far from sufficient to meet the demand, leading to a major organ shortage crisis. To solve this problem, researchers have turned to pigs as their target since pigs have many advantages as xenograft donors. Pigs are considered the ideal organ donor for human xenotransplantation, but direct transplantation of porcine organs to humans faces many obstacles, such as hyperacute rejection, acute humoral xenograft rejection, coagulation dysregulation, inflammatory response, coagulation dysregulation, and endogenous porcine retroviral infection. Many transgenic strategies have been developed to overcome these obstacles. This review provides an overview of current advances in genetically modified pigs for xenotransplantation. Future genetic engineering-based delivery of safe and effective organs and tissues for xenotransplantation remains our goal.